2023
DOI: 10.1093/rasti/rzad034
|View full text |Cite
|
Sign up to set email alerts
|

Synergies between interstellar dust and heliospheric science with an interstellar probe

Abstract: We discuss the synergies between heliospheric and dust science, the open science questions, the technological endeavors and programmatic aspects that are important to maintain or develop in the decade to come. In particular, we illustrate how we can use interstellar dust in the solar system as a tracer for the (dynamic) heliosphere properties, and emphasize the fairly unexplored, but potentially important science question of the role of cosmic dust in heliospheric and astrospheric physics. We show that an Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…A detailed analysis of the detection conditions for interplanetary and interstellar dust with DDA was given in [41,42] and a recent review about interstellar dust in the solar system can be found in [43]. Science questions for interstellar dust and related to the dust-heliosphere interaction can be found in [44].…”
Section: Interplanetary Space At 1 Aumentioning
confidence: 99%
“…A detailed analysis of the detection conditions for interplanetary and interstellar dust with DDA was given in [41,42] and a recent review about interstellar dust in the solar system can be found in [43]. Science questions for interstellar dust and related to the dust-heliosphere interaction can be found in [44].…”
Section: Interplanetary Space At 1 Aumentioning
confidence: 99%